In vitro and in vivo evaluations of a hydrophilic 64Cu-bis(thiosemicarbazonato)-glucose conjugate for hypoxia imaging. - Bayly, SR; King, R; Honess, D; Barnard, P; Betts, H; Holland, J; Hueting, R; Bonnitcha, P; Dilworth, JR; Aigbirhio, F; Christlieb, M (2008)
UNLABELLED: A water-soluble glucose conjugate of the hypoxia tracer 64Cu-diacetyl-bis(N4-methylthiosemicarbazone) (64Cu-ATSM) was synthesized and radiolabeled (64Cu-ATSE/A-G). Here we report our initial biological experiments with 64Cu-ATSE/A-G and compare the results with those obtained for 64Cu-ATSM and 18F-FDG. METHODS: The uptake of 64Cu-ATSE/A-G and 64Cu-ATSM into HeLa cells in vitro was investigated at a range of dissolved oxygen concentrations representing normoxia, hypoxia, and anoxia. Small-animal PET with 64Cu-ATSE/A-G was performed in male BDIX rats implanted with P22 syngeneic carcinosarcomas. Images of 64Cu-ATSM and 18F-FDG were obtained in the same model for comparison. RESULTS: 64CuATSE/A-G showed oxygen concentration-dependent uptake in vitro and, under anoxic conditions, showed slightly lower levels of cellular uptake than 64Cu-ATSM; uptake levels under hypoxic conditions were also lower. Whereas the normoxic uptake of 64Cu-ATSM increased linearly over time, 64Cu-ATSE/A-G uptake remained at low levels over the entire time course. In the PET study, 64CuATSE/A-G showed good tumor uptake and a biodistribution pattern substantially different from that of each of the controls. In marked contrast to the findings for 64Cu-ATSM, renal clearance and accumulation in the bladder were observed. 64Cu-ATSE/A-G did not display the characteristic brain and heart uptake of 18F-FDG. CONCLUSION: The in vitro cell uptake studies demonstrated that 64Cu-ATSE/A-G retained hypoxia selectivity and had improved characteristics when compared with 64Cu-ATSM. The in vivo PET results indicated a difference in the excretion pathways, with a shift from primarily hepatointestinal for 64Cu-ATSM to partially renal with 64Cu-ATSE/A-G. This finding is consistent with the hydrophilic nature of the glucose conjugate. A comparison with 18F-FDG PET results revealed that 64Cu-ATSE/A-G was not a surrogate for glucose metabolism. We have demonstrated that our method for the modification of Cu-bis(thiosemicarbazonato) complexes allows their biodistribution to be modified without negating their hypoxia selectivity or tumor uptake properties.